Acute renal failure associated with albendazole therapy in a patient with trichinosis. (19th May 2014) - Batzlaff, Cassandra Marie; Pupaibool, Jakrapun; Sohail, M Rizwan
Abstract : A 72-year-old Caucasian woman presented with a 3-week history of confusion, cramping abdominal pain, nausea, vomiting, diarrhoea, fatigue and dehydration. By history, she reported consumption of raw pork and bacon that was salted and cured in brine, but not boiled or cooked. Laboratory testing was significant for an absolute eosinophil count of 3.09×10 9 /L. She was found to have a positive Trichinella serology by ELISA testing. Based on history of raw pork consumption, symptoms, peripheral eosinophilia and positive serology, a diagnosis of trichinosis was made. Treatment was started with oral albendazole. Following initiation of therapy, the patient developed acute kidney injury presumably secondary to albendazole. Therapy was discontinued. Her serum creatinine returned to baseline over the following days. The decision was made to proceed with observation alone, as she did not tolerate treatment. At the 3-week follow-up, her gastrointestinal symptoms had improved and her eosinophilia had resolved.